PREDICTING THE JAPANESE YEN'S VOLATILITY IN RELATION TO THE INDONESIAN RUPIAH - Akhmad, Afied; Arnanda, Feza Raffa; Sari, Linda Monica; Kuswardani, Rakaninda Indah; Kartiasih, Fitri (Universitas Gunadarma, 2024)
Japan has experienced low inflation and continuous deflation since the economic bubble of the 1980s. Following the COVID-19 pandemic, the world was preoccupied with deflation in various countries, worsening Japan's financial condition. As a result, the Japanese currency's exchange rate could not compete with other currencies. This situation significantly affects the value of Indonesia's exports and imports, as Japan is one of the leading export destinations and a primary supplier of implications for Indonesia. The purpose of this study is to forecast the volatility of the exchange rate between the yen and the IDR for the future. The data used in this research is the buying rate variable from the yen to IDR exchange rate data from January 3, 2020, to November 27, 2023. The method used for the high-volatility data is the GARCH model. The best modeling obtained is GARCH(0,1). The forecast results provide an insight into the buying exchange rate of the yen against the IDR until the beginning of 2024.